Mini-David procedure. Procedural considerations - Jakub Staromłyński; Mariusz Kowalewski; Wojciech Sarnowski; Radosław Smoczyński; Anna Witkowska; Maciej Bartczak; Jakub Brączkowski; Dominik Drobiński; Piotr Suwalski (Termedia Publishing House, 2022)
The main goal of minimally invasive surgery is to reduce the perioperative trauma, accelerate patient mobilization and reduce the length of hospital stay. Due to the development of modern technology, these treatments can be offered to a wider group of patients. For many years, aortic root surgery consisted of mechanical conduit implantation and, therefore, necessitated life-long anticoagulation. At present, in patients with aortic root aneurysm and significant aortic valve regurgitation, it is possible to perform minimal-access valve sparing surgical procedures. The current paper is a brief description of the surgical technique for aortic root aneurysm surgery with preservation of the patient's own valve using the David procedure.